101 What degree of pulmonary hypertension predicts poor outcome in patients with left ventricular systolic dysfunction? A 10-year follow-up study. (9th June 2011) - Szwejkowski, B R; Elder, D H J; Choy, A M J; Pringle, S D; Struthers, A D; Lang, C C
Abstract : Introduction: The presence of pulmonary hypertension in left ventricular systolic dysfunction (LVSD) is an ominous sign. It remains unclear the level at which pulmonary hypertension conveys a mortality risk in patients with LVSD. Methods: We performed a record-linkage study in Tayside, UK (population approximately 400 000) utilising the Tayside echocardiogram database (>100 000 echo's) maintained by the Health Informatics Centre (HIC). Datasets from HIC include mortality data and other health care activities linked anonymously by the community health index (CHI) number. Patients were included in the analysis if they had LVSD and had a right ventricular systolic pressure (RVSP) measurement. Cox proportional hazards regression analysis was used to examine the effects of different ranges of RVSP measures on all cause mortality. Results: 2910 patients (mean age, 74.5±11.4 years; 43 % male) met entry criteria. Mean RVSP was 43.3 ± 12.7 mm Hg and median follow was 362 days (IQR 129–850 days). There was a significant correlation between RVSP and survival (p<0.0001). In quartiles of RVSP, the HR after adjustment for confounding factors including LVSD and the presence of chronic obstructive pulmonary disease (COPD) were: RVSP 35–41 mm Hg, HR 1.12 (95% CI 0.95 to 1.32, p=0.175), RVSP 42–50 mm Hg, 1.27 (1.07 to 1.49, p<0.001) and RVSP 51–106 mm Hg 1.62 (1.38 to 1.1, p<0.001). For each 5 mm Hg stepwise increase in RVSP the HR for all cause mortality was 1.07 (1.04 to 1.09, p<0.001). Abstract 101 figure 1 shows the Kaplan-Meier survival curves for all cause mortality for all patients expressed as different RVSP quartiles. Conclusion: An RVSP of greater than 42 mm Hg is predictive of increased mortality in heart failure. This is finding is independent of LVSD and COPD.